Sex and society in early twentieth-century Spain : Hildegart Rodríguez and the World League for Sexual Reform - Sinclair, Alison, 1946- (Iberian and Latin American studies., 2007)
This book examines issues of sex and society in early twentieth-century Spain, and does so by using a specific case history, namely that of Hildegart Rodríguez (1914-1933) who came to be one of the central players in the Spanish chapter of the World League for Sexual Reform (WLSR). In all its diversity and with all its inbuilt contradictions the movement provides the complex backcloth for understanding the nature and activity of Hildegart, while her life in its turn demonstrates how the divers strands of the movement led to paradox and conflict. In addition to this Hildegart's correspondence w.